Pengaruh Media Pembelajaran Berbasis Wordwall Terhadap Pemahaman Pembelajaran Bahasa Arab - Muhammad Rifqi Maulana; Aliwafa Aliwafa; Nur Sjamsuarini Pudji Astutik (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to examine the effect of using Wordwall-based learning media on students’ Arabic language comprehension at MTsN 4 Sidoarjo. A quasi-experimental research design with a pretest–posttest approach was employed involving 15 eighth-grade students as participants. Data were collected through pretest and posttest items and analyzed using descriptive statistics and a paired samples t-test. The findings reveal a substantial improvement in students’ learning outcomes after the implementation of Wordwall. The mean score increased from 67.33 on the pretest to 83.20 on the posttest, with a gain of 15.87 points. Furthermore, the standard deviation decreased from 7.088 to 3.364, indicating more consistent student performance after the intervention. The paired samples t-test obtained a t-value of –9.134 with a significance level of p = 0.000 (p < 0.05), confirming that Wordwall had a significant effect on improving Arabic language comprehension. These results demonstrate that Wordwall is an effective digital learning medium for enhancing vocabulary mastery, understanding of language structure, and overall Arabic learning achievement at the secondary level.